Pelatihan Penyusunan Perangkat Pembelajaran Interaktif Matematika SD Berbantuan Generative AI (Chatgpt & Canva) Bagi Guru MI Babusalam - Febriarsita Eka Sasmita; She Fira Azka Arifin; Pance Mariati; Ummu Khairiyah (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service program aimed to enhance the competence of teachers at MI Babusalam Krian in developing elementary mathematics learning materials using Artificial Intelligence (AI). The program included two days of face-to-face training followed by one month of online mentoring through lectures, demonstrations, practical exercises, and group assistance. A total of 18 teachers participated. The results demonstrated a significant improvement in teachers’ competence, with the average pretest score increasing from 52.8 to 78.4 (48.5%). All participants successfully produced complete learning material packages, including lesson plans, student worksheets, instructional media, and assessment instruments, with an average quality score of 82.4. Furthermore, 88.9% of participants implemented the developed materials in their classrooms. Participant satisfaction was very high, with an average score of 4.6 out of 5. Overall, the program effectively strengthened teachers’ competencies and improved the quality of elementary mathematics learning at MI Babusalam Krian.